Investigations of the spreading of falling liquid films in inclined tubes. (April 2018) - Eichinger, S.; Storch, T.; Grab, T.; Fieback, T.; Gross, U.
Highlights: Falling propane films inside vertical and inclined ( ⩽ 20 ° ) smooth/structured tubes. Structuring of inclined tubes surface leads to an enlargement of the wetted area. Wetting rate up to 10 (C3 H8 and H2 O) times higher compared to inclined smooth tube. Film spreading mainly influenced by capillary transport in the grooves. Capillary transport in grooves described with two adapted theoretical models. Abstract: Starting with an extensive literature review, in this study investigations of the film spreading of falling films inside smooth and structured tubes are presented in dependence of the tube inclination angle ( β  = 0° til 20° from the vertical), mass flow rate and fluid temperature (263.15–293.15 K). Experiments are conducted at isothermal conditions and at partly film evaporation as well. The liquid film is observed visually with a camera which can be moved along the total flow length of the liquid without essential disturbance of the liquid respectively gas flow. The liquid used for the investigations is propane ( Pr   ≈  3, Ka   ≈  20 ·  10 10, Re smooth tube  = 20–950). The experiments reveal that the investigated helically structuring of the internal tube surface leads to an improvement of film spreading even for inclination angles up to β  = 20°. Preliminary tests in an open air-water system clearly showed that the groove structure geometry has an influence on initial wetting and film spreading. Further, the results of the calculated capillary transport from two theoretical approaches are compared and adapted to each other.